Peripheral blood leucocyte zinc depletion in babies with intrauterine growth retardation. Issue 10 (October 1983) - Meadows, N; Ruse, W; Keeling, P W; Scopes, J W; Thompson, R P
Abstract : The zinc content of peripheral blood leucocytes from the cord blood of 63 normal and 20 preterm babies, and of 27 babies with evidence of idiopathic intrauterine growth retardation (IUGR) was measured. Leucocyte zinc depletion was present in babies with acute IUGR (IUGR babies compared with controls, mean 47.8 v 51.5 ng zinc/mg dry weight), but was especially severe in those with prolonged IUGR (mean 43.2 ng zinc/mg dry weight), while preterm babies were normal (mean 51.9 ng zinc/mg dry weight). We suggest that this fetal tissue zinc depletion is caused by maternal zinc depletion, and may reflect a reduction of whole body zinc status.